Fiscal and monetary policies to reduce inflation rate in Indonesia - Jaka Sriyana (Jurnal Kebijakan Ekonomi dan Keuangan, 2022)
Abstract Purpose – This paper analyzes the fiscal and monetary policies to control the inflation rate in Indonesia. Methods – This study uses a vector error correction model (VECM) to estimate the inflation model based on the annual data from 1991-2020. Findings – The results present the significant effects of fiscal and monetary variables on the inflation rate. These findings reveal that the fiscal and monetary policies are inflationary in this country. Specifically, government spending and narrow money significantly contribute to the increase in the inflation rate. The research also finds the impacts of those variables have occurred over a long period. This study asserts that the government budget deficit does not affect the domestic price level. This paper concludes that domestic inflation is closely related to both the fiscal and monetary financial sectors. Implication – The government, as well as the central bank, should apply prudent economic policies to control the inflation rate. Originality –This paper confirms the Fiscal Theory of Price Level (FTPL) as well as the quantity theory of money or the Cambridge equation. Abstrak Tujuan – Artikel ini menganalisis kebijakan fiskal dan moneter untuk mengendalikan laju inflasi di Indonesia. Metode – Penelitian ini menggunakan model VECM untuk menganalisis model inflasi berdasarkan data tahunan dari tahun 1991-2020. Temuan – Hasil analisis menunjukkan pengaruh signifikan variabel fiskal dan moneter terhadap tingkat inflasi. Temuan ini mengungkapkan bahwa kebijakan fiskal dan moneter bersifat inflasioner. Secara khusus, pengeluaran pemerintah dan uang sempit berkontribusi secara signifikan terhadap peningkatan tingkat inflasi. Penelitian ini juga menemukan bahwa dampak dari kebijakan tersebut telah terjadi dalam jangka waktu yang lama. Studi ini juga menemukan bahwa defisit anggaran pemerintah tidak mempengaruhi tingkat harga domestik. Hasil penelitian ini menyimpulkan bahwa inflasi domestik terkait erat dengan sektor keuangan fiskal dan moneter. Implikasi – Pemerintah serta bank sentral harus menerapkan kebijakan ekonomi yang hati-hati dan bersifat ketat untuk mengendalikan tingkat inflasi. Orisinalitas – Hasil studi ini mendukung teori fiskal penyebab inflasi (Fiscal Theory of Price Level) dan teori kuantitas uang atau persamaan Cambridge.